The Impact of Capital Market on New Quality Productivity - Mo, Yang (Transactions on Economics, Business and Management Research, 2024)
The establishment of an innovation system centered on New Quality Productivity holds significant implications for China in accelerating the realization of high-level technological self-reliance and the development of high-quality capabilities. This paper empirically examines the role of capital markets in influencing the development of New Quality Productivity by using technological innovation and industrial upgrading as two core proxies and measuring the data at the provincial level in China from 2007 to 2022. The regression results show that the capital market has a significant positive impact on both technological innovation and industrial upgrading with obvious regional differences. From the perspective of technological innovation, the influence of the capital market on the development of New Quality Productivity shows the pattern of “east > central > west”, while from the perspective of industrial upgrading, the influence of the capital market on the development of New Quality Productivity shows the pattern of “central > east > west”. The above findings expand the scope of research on New Quality Productivity and provide important theoretical references for local governments in macro-control and policy formulation.